The Effect of Brand Image and Perceived Price on Smartphone Purchase Intention (Case Study on Samsung Brand) - Vandini Putri (Politeknik Negeri Bandung, 2018)
A few decades ago, the usage of Smartphone has become a new lifestyle. Customers have a complex decisionmaking and many factors that are possible to influence their intention to buy. Thus, in this situation, evaluatewhat drives Smartphone purchase intention is important. There are many companies involved in the competitionbetween Smartphone brands, one of them is Samsung. Samsung is a Korean company that sells manySmartphones, although it has competition Samsung becomes a market leader in the Smartphone business. Inbrief, the researcher will examine how the influence of brand image and perceived price on Smartphonepurchases intention (Samsung case study). This study used 394 respondents who are consumers who have aSmartphone and will buy a Smartphone. Testing data conducted by the researcher are a test of validity,reliability, descriptive statistics, multicollinearity and multiple regression tests. The result of this study is brandimage variable has a significant influence on purchase intention. Meanwhile, the perceived price has not affecttoward purchase intention. These findings give a new insight regarding perceived price is associated withperceived quality, especially in the case of high involvement product as well as the famous brand with a highqualityproduct. Therefore, the brand image considers as important to consumer purchase intention, while theprice is not.